"Imagine if I'm not here, what they're going to do?"—Health‐care access and culturally and linguistically diverse women in prison. (12th September 2018) - Watt, Kelly; Hu, Wendy; Magin, Parker; Abbott, Penny
Abstract: Background: Women in prison have complex medical needs and poorer health status than the general population. Culturally and linguistically diverse (CALD) women in prison, particularly those with limited English proficiency (LEP), have distinct needs and risk additional isolation, discrimination and marginalization when they are in prison. Objective: We sought to examine how cultural and linguistic diversity, particularly LEP, affects the health‐care experiences of women in prison. Design, Setting and Participants: We conducted focus groups and semi‐structured qualitative interviews with CALD women and frontline nursing staff in the three female Correctional Centres in New South Wales, Australia. Results: Participants comprised 30 women in prison and nine nurses. Both women and staff reported communication difficulties as a significant and additional barrier to accessing and receiving health care. For some women with LEP, barriers to care were perceived as discrimination. Fellow prisoners were often utilized as support persons and informal interpreters ("peer interpreters") in place of formally trained interpreters. While peer interpreters were perceived as useful, potential challenges to their use were vulnerability to coercion, loss of confidentiality, untrained health advice and errors of interpretation. Conclusion: The persistent use of peer interpreters in prison is complicated by the lack of clearly defined roles, which can include informal peer support roles and lay health advice. These are highly complex roles for which they are unlikely to be adequately trained or supported, despite perceived benefits to their use. Improved understanding and facilitation of health‐related communication could enhance equity of access for CALD women in prison.